Penerapan Metode Weighted Product Untuk Menganalisis Faktor Pemilihan Pembayaran Digital Transaction Pada Aplikasi Ojek Online - Ratna Fitria; Syifa Nur Rakhmah (Jurnal Teknika, 2019)
This report was conducted to measure the effectiveness of using digital transaction payments on online motorcycle taxis. Where online motorcycle taxi passengers use more digital money than cash as a means of payment. By using criteria on ISO 9001: 2008 factors that influence customer satisfaction include Service Quality, Product Quality, Price, Situational Factor, Personal Factor. This research was conducted on online motorcycle taxi customers in Bekasi regency whose population of 3,500,023 thousand from 23 sub-districts using Slovin calculations found a total sample of 400 respondents. The method used is the weighted product method. The results of this study indicate that the best alternative in digital money is OVO with a value of 0.64 and GO-PAY with a value of 0.36 and for the criteria that attract online motorcycle taxi customers using digital transaction payments, Price with 85% percentage, Situational 90% factor, 87% Personal Factor, 84% Product Quality and 84% Service Quality.